Impact of Jupiter’s Heating and Self-shadowing on the Jovian Circumplanetary Disk Structure - Antoine Schneeberger; Olivier Mousis (The Planetary Science Journal)
Deciphering the structure of the circumplanetary disk (CPD) that surrounded Jupiter at the end of its formation is key to understanding how the Galilean moons formed. Three-dimensional hydrodynamic simulations have shown that this disk was optically thick and significantly heated to very high temperatures owing to the intense radiation emitted by the hot, young planet. Analyzing the impact of Jupiter’s radiative heating and shadowing on the structure of the CPD can provide valuable insights into the conditions that shaped the formation of the Galilean moons. To assess the impact of Jupiter’s radiative heating and shadowing, we have developed a two-dimensional quasi-stationary CPD model and used a gray atmosphere radiative transfer method to determine the thermal structure of the disk. We find that the CPD self-shadowing has a significant effect, with a temperature drop of approximately 100 K in the shadowed zone compared to the surrounding areas. This shadowed zone, located around 10 Jupiter radii, can act as a cold trap for volatile species such as NH _3 , CO _2 , and H _2 S. The existence of these shadows in Jupiter’s CPD may have influenced the composition of the building blocks of the Galilean moons, potentially shaping their formation and characteristics. Our study suggests that the thermal structure of Jupiter’s CPD, particularly the presence of cold traps due to self-shadowing, may have played a crucial role in the formation and composition of the Galilean moons.